Identifikasi Kesulitan Guru IPA Dalam Melaksanakan Pembelajaran Kurikulum 2013 Di SMP Negeri 1 Wonogiri Tahun Pelajaran 2014/2015 - Dewantari, Puspita Mayang Arum; , Dra. Hariyatmi, M.Si (2015)
Learning process in 2013 curriculum was conducted using scientific approach. One of requirements in creating learning 2013 curriculum is by the presence of changing paradigm by the teachers in learning process. This research is aimed to identify the difficulty of science teacher learning in implementing 2013 curriculum in SMP 1 Wonogiri, technique to collect the data are lesson plans documentation, observation class, and interview with science teacher in SMP 1 Wonogiri. The data is collected in the form of descriptive science teacher learning difficulty in implementing 2013 curriculum. The result of the research showed that the teacher difficulties in forming lesson plan are the teacher is hard to form the proper goal of learning (37,5 %), choosing the suitable material (12,5%), choosing and using learning sources optimum (25%), and choosing method/the proper learning model (50%), whereas the difficulty faced by teacher in implementing learning using 2013 curriculum are the teacher has difficulty to do apperception, motivation, and goal of learning (47,92%), mastering learning material (37,50%), doing assesment of learning process and result learning appropriately (47,91%), and implementing steps to close the lesson (50%).